Productivity as a source of economic growth - current situation and prospects in the Republic of North Macedonia - Djambaska, Elizabeta; Lozanoska, Aleksandra; Piperkova, Irina (Institute of Economics-Skopje, 2022)
Today’s world situation has made it difficult for economies to function. Economies continue to struggle with the impacts of the COVID-19 pandemic, first to protect people’s health and also to ensure the recovery of the economy. This current process has been interrupted by the war in Ukraine and all countries must find ways to ensure macroeconomic stability. So, the insurance of economic growth is paramount. Productivity growth is the one of the most important sources and a key factor for sustained economic growth. Economic recovery and an increase in GDP are preconditions for reducing poverty and improving quality of life. Productivity is an indicator of the use (exploitation) of the potential of inputs for creating new value added in the economy. In the long term, productivity growth is dependent upon innovation, investment in physical capital, and investment in human capital. These immediate factors are shaped by the environment in which enterprises operate: market structures, infrastructure, the institutional framework and the quality of governance. The main objective of this paper is to study productivity growth in the Republic of North Macedonia and to analyse and propose measures that can be taken and stimulate productivity. There are two primary ways of measuring productivity: labor productivity and total factor productivity (TFP). Throughout this paper, productivity is considered as output (gross domestic product - GDP) per input of a unit of labour. This concept takes into consideration the number of economic engaged people, rather than the number of working hours as the measures of labour input in the economy. Therefore, the indicator of labour productivity in the Republic of North Macedonia that is calculated yearly and quarterly, is a weighted sum of sector-level productivity as a ration between the value added of a sector and the number of employed persons. The analysis uses the database of State Statistical Office and National Bank of Republic of North Macedonia. Also, the total factor productivity (TFP) is considered in this paper. Productivity calculations use the Solow growth model of economic growth as a function of labour, capital and productivity. As such, TFP measures the effectiveness of combined factor inputs and is often used to represent technological progress. TFP may also incorporate wider factors such as organizational and institutional characteristics. TFP is also widely known as a Solow’ residual. The calculations of the TFP for the previous period of 2000-2020 are presented in this paper. These two aspects cover the productivity in macroeconomic contexts. The other crucial aspect in the analysis of productivity is the level of productivity of the enterprise. The Enterprise Survey conducted by the World Bank in 2009, 2013 and 2019 include 360 enterprises in North Macedonia. The Survey covers the question about labour productivity growth by year. This measure that explains the performance of the enterprises is essential to the conclusions about the productivity in firms. Evaluating employee perceptions of productivity and recent changes in work due to COVID-19 is also valuable for the overall state. Hence, the questions on productivity were part of the online survey distributed among employees in North Macedonia. The findings from the received responses are also included here. Labour productivity in North Macedonia is low, and in the past five years even negative. Quarterly, the labour productivity shows the lowest values in the 2020 which is the year of the pandemic and cannot be referenced for comparison. Besides that, the labour productivity is with low level and mostly with negative values in the whole analyzed period (2012–2020). The calculations of the total factor productivity using the Solow’s growth model and Cobb-Douglas production function for the past twenty years, shows that GDP average growth is 4,97% and the TFP contribute by 1,69%. Therefore, the expectations for the increase of the GDP and reaching economic growth that can be sustainable is possible with increasing total factor productivity in the North Macedonia.
Keywords: economic growth, labour productivity, total factor productivity, firm productivity